(3OjhGf GdTQja GdQVjs - (3eMeO Hf GdMSjf Hf ehSi GdYdhj GdMSjfj GdehShj, GdTQja GdQVj , CHh GdMSf,J (B406 (3g` s
(3ChdgG (B:s
(3HGH GdeOjM bGajI GdgeRI bGd jeOM GdNdjaI GdWGFY ddg(B: (3LRGA CejQ GdeDefjf KfGFj Ydi fYe eG JfbVj hYWGA s
(3BNQgG (B:s
(3bGajI GdjGA GdeaQOGJ EPG fSH GdfLGM Edi ShGge ZOG ajge hEf cQehG OYjG s
(3UfYI CHj GdMcje YHOGddg Hf EHQGgje GdNHQjs
(3ocJHJ GdfSNI HYO GdNeSeGFIs
(3gPg GdUfYI JeJGR HRjGOGJs
(3hQOJ CjVkG JMJ (B2191(3, (B2244(3, (B70(3, (B725s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B99 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B261s
Keywords: (3GdCOHs